Kurt Weill’s Deadly Sins in Copenhagen : A thistle in the Danish kitchen garden of 1936 - Krabbe, Niels (Danish Yearbook of Musicology, 2012)
Kurt Weill’s The Seven Deadly Sins to a text by Bertolt Brecht from 1933 marks the end of the stormy collaboration during the six previous years between the two artists. The work was only performed a few times during Weill’s lifetime, and among these the performance at The Royal Theatre in Copenhagen in November 1936 was the one that was given most public attention. Both before and after the performance, the Copenhagen press focused intensively on the work, partly because of its political contents, partly because it was not possible to pigeon hole the work in any of the well known musical and dramatic genres. To this should be added the myth that German interference was the reason why the work was only given two performances in Copenhagen. The article is based on sources in The Royal Theatre and The State Archives in Copenhagen, supplemented with contemporary newspapers.